"OUR FATHER" AND COSMIC CONSCIOUSNESS: INSIGHTS INTO A NEW INTERPRETATION - VINEETH, V. FRANCIS (Asian Horizons, 2007)
The prayer ’Our Father’ brings before us a wider universe, which starts with an inclusive language for all people, and considering all of them as children of a loving father. Nobody is excluded, by way of country, culture and religion. All can pray this prayer of unity with a universal consciousness that we all are children of one Father in heaven. It